Comparative effectiveness of packaging design pheromone product to sustainable pest management of rhinoceros beetle in oil palm plantation - Henny Hendarjanti (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2024)
The rhinoceros beetle (Oryctes rhinoceros L.) is the primary pest of oil palm plants. Rhinoceros beetle pest attacks cause severe damage to immature and mature plants. They produce an aggregation pheromone identified as ethyl-4-methyloctanoate (E4-MO). Rhinoceros beetles use this pheromone to find suitable habitats for foraging and breeding in the landscape of oil palm plantations. The mass use of pheromone traps has been used to monitor and capture imago stages of O. rhinoceros in the implementation of integrated pest management. Many commercial E4-MO pheromone products have been developed on the market with different packaging designs. The research aimed to determine packaging designs that increase attractiveness and effectiveness in catching rhinoceros beetles. The research was conducted at an oil palm plantation in Indragiri Hulu Regency, Riau. This research was an experimental method. The four design pheromone (permeable sachet, micropore sachet, tube dispenser and double dispenser) were installed in each oil palm planting block (planting area ± 30 ha/block). The number of installations for each design is three units/block with five replications. The assessment of rhinoceros beetle catches was carried out over four months. The results showed significant differences in the catch of rhinoceros beetles. The 4th month of observations showed that the double dispenser packaging design resulted in a higher total catch of rhinoceros beetles, with an average of 161.40. Meanwhile, permeable sachets, microporous sachets, and tube dispensers were 138.20, 139.80 and 91.00 beetles, respectively. Determining the pheromone packaging design is crucial to providing an effective and efficient pest management strategy.